The Effects of Price, Product Quality, and Lifestyle on Students’ Purchase Decisions: Evidence from Mie Gacoan in Bandar Lampung - Susi Indriyani; Nyoman Tyo Awidianto; Anugerah Sanjaya (CV. Media Digital Publikasi Indonesia, 2026)
The rapid growth of low-cost food and beverage (F&B) businesses in Indonesia has intensified competition, particularly in student-dominated markets. University students represent a unique consumer segment characterized by high price sensitivity, experiential consumption, and lifestyle-oriented preferences. This study examines the effects of price, product quality, and lifestyle on students’ purchase decisions at Mie Gacoan in Bandar Lampung. A quantitative explanatory approach was employed using a cross-sectional survey of 98 university students who had purchased Mie Gacoan products at least twice within the previous month. Data were analyzed using multiple linear regression with SPSS. The results indicate that price, product quality, and lifestyle all have positive and significant effects on purchase decisions, both partially and simultaneously. Among the examined variables, lifestyle emerged as the most dominant determinant, followed by price and product quality. The model demonstrates strong explanatory power, with an adjusted R² value of 0.932. These findings suggest that students’ purchase decisions in low-cost F&B settings are shaped not only by economic considerations but also by experiential and psychographic factors. This study contributes to consumer behavior literature by integrating price perception, product quality, and lifestyle into a single explanatory framework and provides managerial insights for F&B businesses targeting student markets.